2014
DOI: 10.2478/s11687-014-0235-6
|View full text |Cite
|
Sign up to set email alerts
|

First description of male Philometra thaiensis Moravec, Fiala et Dyková, 2004 (Nematoda: Philometridae) from the body cavity of the eyespot pufferfish Tetraodon biocellatus Tirant, and evolutionary relationships of this species with other dracunculoids as inferred from SSU rRNA gene sequences

Abstract: 236 SummaryFinding male philometrid nematodes is essential for taxonomic identification among congeneric species. In this study, male Philometra thaiensis Moravec, Fiala et Dyková, 2004 were collected and described for the first time, from the body cavity of the freshwater fish (eyespot pufferfish) Tetraodon biocellatus Tirant (Tetraodontiformes, Tetraodontidae), and conspecific females were redescribed based on the additional morphological biometrics examined. Molecular examination was carried out on the smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…The present specimens were equipped with typical papillae distributed on their body surface, which are key characteristics of the genus Philometroides [10]. The morphological features (the arrangement of organs and their measurements) seemed well fitted with the morphological characteristics of P. seriolae as described by previous authors [2][3][4]10]. Moravec and Ogawa [2] mentioned that subgravid females show 14 papillae with a pair of amphids arranged in 2 circles.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…The present specimens were equipped with typical papillae distributed on their body surface, which are key characteristics of the genus Philometroides [10]. The morphological features (the arrangement of organs and their measurements) seemed well fitted with the morphological characteristics of P. seriolae as described by previous authors [2][3][4]10]. Moravec and Ogawa [2] mentioned that subgravid females show 14 papillae with a pair of amphids arranged in 2 circles.…”
supporting
confidence: 79%
“…Due to the distinct morphological differences with the genus Philometra Costa, 1845, philometrid nematodes equipped with cuticular bosses have been classified as genus Philometroides. However, the current results based on phylogenetic analysis revealed that cuticular bosses might not be a major key to identify the genus [4]. However, here the genus was retained until the taxonomic status could be revised.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…DNA was eluted in elution buffer and kept at -20°C untiluse. The partial 18S rDNA was amplified by PCR using the primers 35f (forward: 5′-TATAATGGTGAAACCGCGAACGGC-3′) and 18gM (reverse: 5′-GGAAACCTTGTTACGACTTTTGCC-3′) (Quiazon et al 2009). The cox1 region was amplified by PCR using the primers COXIF (forward: 5′-TTTTTTGGTCAT CCTGAG GTTTAT-3′) and COXIR (5′-ACATAATGAAAAT-GACTAACAAC -3′).…”
Section: Molecular Proceduresmentioning
confidence: 99%